Study on the effect of different preparation methods of dope solution on development of polyethersulfone MMMs for O2/N2 separation - Siti Hajar, Mustafar (2012)
The developments in inorganic particles insertion in the polymeric membrane called as mixed matrix membrane (MMMs) have been fundamental to the advances in membranes gas separation technology.The objectives of this study are to develop high performance asymmetric polyethersulfone (PES) mixed matrix membranes for oxygen (O2) and nitrogen (N2) gas separation by manipulating three different methods preparation of dope solution.The asymmetric flat sheet membranes were fabricated via dry/wet phase inversion technique.The polymer solution consists of polyethersulfone as a polymer,1-methyl-2-pyrrolidone (NMP) as a solvent and zeolite 5A as inorganic particles.The modified zeolite was prepared by treating the zeolite 5A with 3-Aminopropyl-Trimethoxysilane (APTMOS) to allow PES chain merged on the zeolite surface.The prepared membrane was coated using Polydimethyl siloxane and n-hexane in order to get the defect free membranes.The performance of membranes was examined using oxygen and nitrogen as test gases. The surface morphology of the prepared membrane was identified using scanning electron microscopy (SEM).The result shows that the best performance for O2/N2 separation was using second method named homogeneous polymeric solution formation where the selectivity was 4.50 while the lowest selectivity is for the third method which is 0.96.The optimum pressure was found at 3 bars.Therefore,it can concluded that by manipulating the different methods of dope solution preparation will influenced on gas separation performances